Cultivate the six non-negotiable traits of a winning team - Bond, Walter 1969-; Bond, Antoinette (John Wiley & Sons, Inc., 2023)
"Cultivate: The Six Non-Negotiable Traits of a Winning Team is a rich and empowering parable that follows three corporate team leaders as they discover how to build an elite corporate team. Throughout the story, the frustrated leaders who are all neighbors in a high-end country club take a casual yet profoundly introspective look into their own character flaws, strengths, fears, habits, and shortcomings and discover firsthand how they impact their team's culture. As the story unfolds each leader discovers they built their culture and it's up to them to manage and improve it. Leadership can't be about you; teamwork is about us. Packed with tried-and-true teamwork fundamentals that are easy to understand and apply, this book will change the way employees and employers think about their people and teamwork. It will dive into the "Six Non-Negotiable Traits" that are a signature of all high-performing teams. After reading this book, employees will have a firm understanding of how to contribute to a high-performing team, and employers will finally have the applicable steps they need to create the ideal culture to attract other high performers."--